Student Responses to Online Learning of Indonesian Language Subjects Based on LMS Moodle - Setyaningsih, Vitria Indriyani; Rahmawati, Laili Etika (Jurnal Penelitian Ilmu Pendidikan, 2021)
This study aims to describe students’ responses to online learning of Indonesian language subjects based on Moodle LMS at SMP Negeri 17 Surakarta. The research approach used is descriptive qualitative research. The subject and object of the study focused on seventh grade students of SMP Negeri 17 Surakarta and Indonesian language teachers. The data collection technique in this study was through interview techniques by distributing questionnaires through Google Forms and literature studies. Data analysis techniques used interactive analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The validity of the data was tested using data triangulation techniques and data sources. The results of this study indicate that the students’ responses to online learning in Indonesian subjects showed a positive response. The questionnaire shows that students feel happy in online learning using the LMS Moodle for Indonesian subjects. The delivery of the subject matter is very easy to understand because the teacher uses animated videos and video teaching materials. The obstacles experienced during the learning process were handled well by the school’s IT team and subject teachers who were very responsive. Respon Siswa terhadap Pembelajaran Daring Mata Pelajaran Bahasa Indonesia Berbasis LMS Moodle Penelitian ini bertujuan untuk mendeskripsikan respons siswa terhadap pembelajaran daring mata pelajaran Bahasa Indonesia berbasis LMS Moodle di SMP Negeri 17 Surakarta. Metode penelitian dilakukan melalui survey pendapat dari siswa menggunakan google form. subjek dan objek penelitian berfokus terhadap siswa kelas VII SMP Negeri 17 Surakarta dan guru Bahasa Indonesia. Teknik pengumpulan data dalam penelitian ini melalui teknik wawancara dengan menyebarkan kuesioner melalui Google Form dan studi pustaka. Teknik analisis data menggunakan teknik analisis interaktif yang terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Uji keabsahan data dilakukan dengan teknik triangulasi data dan sumber data. Hasil penelitian ini yaitu respons siswa terhadap pembelajaran daring mata pelajaran Bahasa Indonesia menunjukkan respons yang positif. Kuesioner menunjukkan, siswa merasa senang dalam pembelajaran daring menggunakan LMS Moodle untuk mata pelajaran Bahasa Indonesia penyampaian materi pelajaran sangat mudah untuk dipahami karena guru menggunakan video animasi dan video bahan ajar. Kendala yang dialami ketika proses pembelajaran pun ditangani dengan baik oleh tim IT sekolah serta guru mata pelajaran yang sangat responsive.